Imperial Policy and Strategic Industry Administration: the Spanish Navy in the Long Eighteenth Century. Introduction - María Baudot Monroy; Manuel Díaz-Ordóñez; Iván Valdez-Bubnov (Espacio, Tiempo y Forma. Serie IV, Historia Moderna, 2019)
Introducción al monografíco